Nonlinear Pounding Analysis of Multispan and Simply Supported Beam Bridges Subjected to Strong Ground Motions - Hong-Yu Jia; Xian-Lin Lan; Nan Luo; Jian Yang; Shi-Xiong Zheng; Chao Zhang (Shock and Vibration)
To investigate the nonlinear impact effect of multispan simply supported beam bridges under strong earthquakes, firstly, the dynamic motion equation, the algorithm of its solution, and some pounding modelling methods are presented and the finite element model of a considered multispan simply supported railway beam bridge is established in the nonlinear finite element software of SAP2000 in which the primary nonlinear characteristics of the bearing and the impact element are considered herein. Secondly, the natural vibration characteristic of the considered railway bridge is analyzed to prepare for the subsequent parameter analysis. Finally, the influence of three nonlinear parameters, i.e., stiffness of impact element, separation gap width of expansion joint, and bearing stiffness, on impact responses of bridge structures is studied. The results show that the first several modes of multispan simply supported beam bridges are mainly longitudinal and vertical vibrations. Under longitudinal seismic excitations, the large longitudinal displacement response is induced possibly and results in the collision or even unseating of superstructures at the expansion joints and abutments. The influence of separation gap width between adjacent decks on the pounding effect of bridges is greater than that of collision stiffness originated from the pounding modelling element. The impact force and pounding number run up to the maximum conditional on the collision stiffness of 9.9 × 109 (N/m) and the separation gap width of 0.14 (m). The bearing stiffness affects significantly the displacement of the pier top and the cross-sectional internal force at the bottom of piers but has little effect on the collision force and number.